Early-Stage Lung Cancer Patients' Perceptions of Presurgical Discussions. Issue 1 (March 2022) - Schwartz, Rebecca M.; Yip, Rowena; You, Nan; Gillezeau, Christina; Song, Kimberly; Yankelevitz, David F.; Taioli, Emanuela; Henschke, Claudia I.; Flores, Raja M.; ,
Background: Patients with early-stage non–small-cell lung cancer (NSCLC) have high survival rates, but patients often say they did not anticipate the effect of the surgery on their postsurgical quality of life (QoL). This study adds to the literature regarding patient and surgeon interactions and highlights the areas where the current approach is not providing good communication. Design: Since its start in 2016, the Initiative for Early Lung Cancer Research on Treatment (IELCART), a prospective cohort study, has enrolled 543 patients who underwent surgery for stage I NSCLC within the Mount Sinai Health System. Presurgical patient and surgeon surveys were available for 314 patients, postsurgical surveys for 420, and both pre- and postsurgical surveys for 285. Results: Of patients with presurgical surveys, 31.2% said that their surgeon recommended multiple types of treatment. Of patients with postsurgical surveys, 85.0% felt very well prepared and 11.4% moderately well prepared for their postsurgical recovery. The median Functional Assessment of Cancer Therapy–Lung Cancer score and social support score of the patients who felt very well prepared was significantly higher than those moderately or not well prepared (24.0 v. 22.0, P < 0.001) and (5.0 [interquartile range: 4.7–5.0] v. 5.0 [IQR: 4.2–5.0], p = 0.015). Conclusions: This study provides insight into the areas where surgeons are communicating well with their patients as well as the areas where patients still feel uninformed. Most surgeons feel that they prepare their patients well or very well for surgical recovery, whereas some patients still feel that their surgeons did not prepare them well for postsurgical recovery. Surgeons may want to spend additional time emphasizing postsurgical recovery and QoL with their patients or provide their patients with additional avenues to get their questions and concerns addressed. Highlights: Pretreatment discussions could help surgeons understand patient priorities and patients understand the anticipated outcomes for their surgeries. There is an association between feeling prepared for surgery and higher quality of life and social support scores after adjustment for confounders. Despite these pretreatment discussions, patients still feel that they are not well prepared about what to expect during their postsurgical recovery.